Polymorphous low grade adenocarcinoma in oral cavity: a case report (Bangladesh Journal of Otorhinolaryngology, 2010)
Polymorphous low grade adenocarcinoma is a slow growing tumor mainly arises in minorsalivary glands in oral cavity. The frequency of regional lymph node and distant metastasis arevery low in this tumor. Careful examination of histolopathological specimen is necessary asfeatures frequently overlap with that of pleomorphic adenoma and adenoid cystic carcinoma.Local excision is the treatment of this condition. Recurrences and distant metastasis werereported in literature many years after surgery. So, long term regular follow up is required inthis group of patients.DOI: 10.3329/bjo.v16i1.5784Bangladesh J Otorhinolaryngol 2010; 16(1): 66-69